Evidence for the impact of interventions and medicines reconciliation on problematic polypharmacy in the UK: A rapid review of systematic reviews. Issue 1 (5th July 2020) - Martyn‐St James, Marrissa; Faria, Rita; Wong, Ruth; Scope, Alison
Abstract : This was a rapid review of systematic reviews (SRs) on problematic polypharmacy (PP) in the UK. The commissioner‐defined topics were burden of PP, interventions to reduce PP, implementation activities to increase uptake of interventions, and efficient handover between primary and secondary care to reduce PP. Databases including Medline were searched to June 2019, SR quality was assessed using AMSTAR‐2 (A MeaSurement Tool to Assess systematic Reviews) and a narrative synthesis was undertaken. Except for burden of PP (SRs had to include UK studies), there were no restrictions on country, location of care or outcomes. Nine SRs were included. On burden, three SRs (including six UK studies) found a high prevalence of polypharmacy in long term care. PP was associated with mortality, although unclear if causal, with no information on costs or health consequences. On interventions, six reviews (27 UK studies) found that interventions can reduce PP, but no effects on health outcomes. On handover between primary and secondary care, one review (two UK studies) found medicine reconciliation activities to reduce medication discrepancies at care transitions reduce PP, although the evidence is low quality. No SRs on implementation activities to increase uptake of interventions were found. SR quality was variable, with some concerns regarding meta‐analysis methods. Evidence of the extent of PP in the UK, and what interventions to address it are effective in the UK, is limited. Future UK research is needed on the prevalence and consequences of PP, the effectiveness and cost‐effectiveness of interventions to reduce PP, and barriers and activities to ensure uptake.